The effect of physical exercise and diet and a reduction of oxygen in some behavioral disorders of autistic children ( Comparative Study - Ali, Suha (Journal of Physical Education, 2015)
Autism terms of growth ,usually appear during the first three years of a child’s life, which is caused by a disorder of the nervous system which affects the brain functions, and increased incidence among boys than girls by 4-1, this disorder is associated with any ethnic factors, or social, where it is proved that the person’s race or social class or educational or financial situation of any family relationship injury autism, the aim of the study: Number of physical exercises for a group of children who suffer from autism program. - Use diet program for a group of children who suffer from autism. - Use the program of hyperbaric oxygen therapy to a group of children who suffer from autism. To identify the differences between tribal tests and a posteriori the research sample. To identify the differences between the three programs designed experimental groups. Was used experimental method for suitability to the nature of the research, was used behavioral disorders scale, The researcher using three programs, namely, (motor program - diet - oxygen therapy) and conducted a comparative study between the three programs were conclusions are that the three programs have been successful in reducing behavioral disorders the research sample, but to varying degrees, where the best results for the treatment of diet programs , kinetic therapy, and then oxygen therapy